Academic Single Mothering during a Pandemic - Ségeral, Nathalie (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Mothering during the pandemic has crystallized the preexisting gender gap in academia. Whereas previous studies have shown that women with children are significantly less likely to achieve full professorship than their childless or male peers, recent studies have already found evidence of a gender gap in productivity during the pandemic and several articles have been published on this topic by academic mothers struggling with having to juggle childcare, homeschooling, and academic duties from home. However, these papers and studies focus on partnered academic mothers, further exacerbating the invisibility of single mothers. Using my own experience as a single mother to five-year-old twin boys who left an American university for an Australian one during the pandemic, along with experiential accounts by other single academic mothers from the Facebook group “Single Parents in Academia,” this chapter highlights the specific challenges faced by single mothers during COVID-19 in a transnational context, both in and outside of academia. It also suggests avenues for solutions and improved policies to mitigate the single motherhood double penalty through a comparison of the lockdown regulations across three countries (France, the United States, and Australia). Its goal is to give visibility to single mothering, which has been further marginalized by the pandemic and its accompanying media discourse and emergency measures.